FORMING OF THE INTERCULTURAL COMPETENCE OF FUTURE DENTISTS - Kulbashna, Yaroslava A. (Educological discourse, 2014)
This article discusses the formation of intercultural component of international professional competence of future dentists. The need for such studies is associated with increased numbers of foreign students, a splash of multiculturalism in society in general, and in higher medical schools, the process of active implementation of the principle of academic mobility in higher education in Ukraine.